Today's moral issues : classic and contemporary perspectives - Bomevac, Daniel (McGraw-Hill, 2012)
This book is about moral issues. What are moral issues? To answer this questions, we need to consider the definition of philosophy. If the word itself is any guide, philosophy is the love of wisdom. A simple definition of wisdom, in turn, is good judgment. Moral philosophy, or ethics, is the pursuit of good judment about character and action-about what kind of person to be and about what to do. Ethics addresses questions about virtue and vice, good and bad, right and wrong....